2020
DOI: 10.1021/acs.jafc.0c01240
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotic Effect of Whole Grape Seed Flour and Newly Isolated Kefir Lactic Acid Bacteria on Intestinal Microbiota of Diet-Induced Obese Mice

Abstract: Alterations of intestinal microbiota by synbiotic action of pre- and probiotics may confer health benefits to the host. In this study, high-throughput sequencing of 16S rRNA was used to analyze intestinal microbiota in feces, and the relative abundance of intestinal bacteria was correlated with physiological data from a prior study of a synbiotic combination of flavonoid-rich wine grape seed flour (WGF) and two newly isolated kefir lactic acid bacteria (LAB) in diet-induced obese mice. The combination of WGF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…What scientists found was an increased F/B ratio in obese versus lean samples (Moran‐Ramos et al, 2017). Also, LAB that can alleviate obesity generally reduces the F/B ratio and raise the diversity of gut microbiota (K. H. Seo et al, 2020). L. plantarum LC27 were reported to alleviate obesity in mice with the effect of reducing Firmicutes and Proteobacteria abundance in gut microbiota and lipopolysaccharide (LPS) production (In Kim et al, 2019).…”
Section: Effects Of Lab Intervention On Gut Microbiota Results In Wei...mentioning
confidence: 99%
“…What scientists found was an increased F/B ratio in obese versus lean samples (Moran‐Ramos et al, 2017). Also, LAB that can alleviate obesity generally reduces the F/B ratio and raise the diversity of gut microbiota (K. H. Seo et al, 2020). L. plantarum LC27 were reported to alleviate obesity in mice with the effect of reducing Firmicutes and Proteobacteria abundance in gut microbiota and lipopolysaccharide (LPS) production (In Kim et al, 2019).…”
Section: Effects Of Lab Intervention On Gut Microbiota Results In Wei...mentioning
confidence: 99%
“…In contrast, the richness of microflora severely decreased after treatment with kanamycin, the Chao1 index decreased from 957.83 to 355.77, and the Shannon index decreased from 4.92 to 4.23. The results indicated that oral antibiotics for 3 days significantly decreased the diversity of intestinal microflora in mice, whereas d -Au NPs cannot affect the richness and evenness of intestinal microflora [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that the consumption of 5% kefiran (EPS extracted from kefir grain) prevented high fat-induced obesity in an animal model [ 29 ], which was associated with the modulation of intestinal microbiota. L. kefiri DH5 (LKDH5) and L. mesenteroides 4 (LMDH04) used for present animal study showed the greatest inhibitory pancreatic lipase activity [ 33 ]. Tannin polyphenols enriched in GSF have an inhibitory pancreatic lipase activity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%